2019
DOI: 10.3389/fnhum.2018.00542
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Brain-Level Interactions Between Visuospatial Attentional Demands and Working Memory Load While Driving Using Functional Near-Infrared Spectroscopy

Abstract: Driving is a complex task concurrently drawing on multiple cognitive resources. Yet, there is a lack of studies investigating interactions at the brain-level among different driving subtasks in dual-tasking. This study investigates how visuospatial attentional demands related to increased driving difficulty interacts with different working memory load (WML) levels at the brain level. Using multichannel whole-head high density functional near-infrared spectroscopy (fNIRS) brain activation measurements, we aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 103 publications
2
37
0
Order By: Relevance
“…These studies in accord with laboratory paradigms have most prominently (though not exclusively) reported a rise of prefrontal activity with rising workload. This link has been reported for several isolated driving maneuvers (lateral prefrontal cortex 41 ), secondary tasks during driving (DLPFC, inferior frontal gyrus/ IFG 42 , 43 ), narrow vs. wide rode driving (DLPFC 42 ) and driving with differing amounts of automation 44 – 46 .…”
Section: Introductionsupporting
confidence: 55%
“…These studies in accord with laboratory paradigms have most prominently (though not exclusively) reported a rise of prefrontal activity with rising workload. This link has been reported for several isolated driving maneuvers (lateral prefrontal cortex 41 ), secondary tasks during driving (DLPFC, inferior frontal gyrus/ IFG 42 , 43 ), narrow vs. wide rode driving (DLPFC 42 ) and driving with differing amounts of automation 44 – 46 .…”
Section: Introductionsupporting
confidence: 55%
“…Six studies reported solely a vague age range (e.g., “in their 20s”) ( Shimizu et al, 2009 ; Tsunashima and Yanagisawa, 2009 ; Takahashi et al, 2010 ; Pradhan et al, 2015 ; Nguyen et al, 2017 ; Chuang et al, 2018 ), and the remaining six studies did not report participants’ ages at all ( Nakano et al, 2013 ; Oka et al, 2015 ; Unni et al, 2015 ; Huve et al, 2018 , 2019 ; Yamamoto et al, 2019 ). Only 18 studies reported driver statistics such as total number of years of driving and frequency of driving ( Harada et al, 2007 ; Tomioka et al, 2009 ; Yoshino et al, 2013a , b ; Oka et al, 2015 ; Orino et al, 2015 , 2017 ; Pradhan et al, 2015 ; Foy et al, 2016 ; Nosrati et al, 2016 ; Xu G. et al, 2017 ; Bruno et al, 2018 ; Foy and Chapman, 2018 ; Li et al, 2018 ; Le et al, 2018 ; Hidalgo-Munoz et al, 2019 ; Scheunemann et al, 2019 ; Sturman and Wiggins, 2019 ). With respect to gender, eight studies did not report participants’ gender distribution ( Li et al, 2009 ; Unni et al, 2015 ; Foy et al, 2016 ; Xu L. et al, 2017 ; Chuang et al, 2018 ; Huve et al, 2018 , 2019 ; Khan et al, 2019 ), 12 studies examined exclusively male participants ( Shang et al, 2007 ; Shimizu et al, 2009 ; Shimizu T. et al, 2011 ; Tomioka et al, 2009 ; Tsunashima and Yanagisawa, 2009 ; Nakano et al, 2013 ; Inoue et al, 2014 ; Khan and Hong, 2015 ; Pradhan et al, 2015 ; Liu et al, 2017 ; Ihme et al, 2018 ; Tanveer et al, 2019 ), and for the remaining 28 studies, the ratio of female to male participants ranged from 10 to 69%, with an average of M ...…”
Section: Methodological Reviewmentioning
confidence: 99%
“…Among the papers reviewed here, 23 did not report information regarding the driving familiarization task used. Participants were allowed to experience the driving environment (simulated or on-road) within 18 studies ( Li et al, 2009 ; Shimizu et al, 2009 ; Liu, 2014 ; Khan and Hong, 2015 ; Pradhan et al, 2015 ; Oka et al, 2015 ; Ahn et al, 2016 ; Foy et al, 2016 ; Sibi et al, 2016 ; Horrey et al, 2017 ; Chuang et al, 2018 ; Ihme et al, 2018 ; Yamamoto et al, 2018 , 2019 ; Khan et al, 2019 ; Lin et al, 2019 ; Sturman and Wiggins, 2019 ; Tanveer et al, 2019 ), and seven studies allowed participants to familiarize themselves with the driving environment and task-related stimuli ( Tsunashima and Yanagisawa, 2009 ; Yoshino et al, 2013a , b ; Unni et al, 2015 ; Balters et al, 2017 ; Sibi et al, 2017 ; Scheunemann et al, 2019 ). Only four studies reported a physiological baseline task (i.e., task designed to allow participants’ cortical activity to settle into a resting level), including sitting quietly with or without eyes open for a period of 2 min ( Zhu et al, 2019 ), 5 min ( Li et al, 2018 ), 10 min ( Li et al, 2009 ), or 20 min ( Xu G. et al, 2017 ).…”
Section: Methodological Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring of vital functions in a car faces many problems with signal distortion due to interference caused by the vehicle and driver himself—for example, movement artifacts [ 75 ]. These artifacts are non-stationary and more prevalent in discrete sensory techniques [ 76 ].…”
Section: Overview Of Already Existing Methodsmentioning
confidence: 99%